2012
DOI: 10.1159/000341879
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen Alpha-Receptor Variant and Two-Year Memory Decline in Midlife Australian Women

Abstract: Objective: To prospectively examine the influence of the oestrogen-α receptor (ESR1)PvuII polymorphism on changes in memory performance over a 2-year period among 80 midlife postmenopausal Australian women. Methods: Healthy women aged 56–67 years were administered a battery of four memory (verbal and non-verbal) tasks at baseline and 2 years later. Results: Carriers of the ESR1 p allele had significantly greater declines in logical memory compared to participants with the PP genotype, independent of demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…In addition the results of our early work have highlighted the importance of longitudinal studies in cognitive research as timing and duration of exposures is relevant to outcomes for blood pressure [140], lipids [141], hormones [142146] and other modifiable risk factors [142]. Genomic associations with early cognitive decline have been examined with the influence of estrogen polymorphism published [147]. There is an absence of published normative data in Australia and the first published normative papers came from the WHAP data set for memory [148] and executive function [149].…”
Section: Resultsmentioning
confidence: 99%
“…In addition the results of our early work have highlighted the importance of longitudinal studies in cognitive research as timing and duration of exposures is relevant to outcomes for blood pressure [140], lipids [141], hormones [142146] and other modifiable risk factors [142]. Genomic associations with early cognitive decline have been examined with the influence of estrogen polymorphism published [147]. There is an absence of published normative data in Australia and the first published normative papers came from the WHAP data set for memory [148] and executive function [149].…”
Section: Resultsmentioning
confidence: 99%
“…A study by Bousmann, which included women aged 56–67, showed that the carriers of TT PvuII obtained the worst results for logical memory, compared to those with CC PvuII, who obtained the best results. The researcher postulates the necessity for further studies in order to prove the hypothesis that the T PvuII allele is the genetic marker of memory disorders [ 46 ]. Yaffe found a significant relationship between A Xbal and/or T PvuII polymorphisms, and lower results for cognitive functions in the Modified Mini-Mental Status Examination (3MS).…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained depended on demographic factors, concomitant diseases, presence of APOE e*4, cigarette smoking and alcohol consumption. In the researcher’s opinion, they are also evidence indicating the need for further studies to confirm that the presence of the T allele of PvuII is a genetic marker of the risk of memory disorders among postmenopausal women [ 80 ]. Sundermann conducted a comprehensive meta-analysis including 14 studies of this issue.…”
Section: Cognitive Functions According To Erα Polymorphisms – Effect mentioning
confidence: 99%